O deslocar de horizontes: um estudo de caso da leitura de textos literários em língua inglesa - Dilys Karen Rees (2003)
This paper focuses on the intellectual understanding of English language literary texts in a classroom of a university públic the Midwest. It is a qualitative study using concepts of ethnography, such as participant observation (Erickso, 1986; Spindler and Spindler, 1992) for the study of the classroom. Seventeen students of the discipline Literature Americanoa II of the fifth year of Portuguese Language / English participated. It lasted two semesters of one academic year in which the class was observed by anotaçõe field, audio recordings and collecting documents. Some students also were you Interview istados. The concept of cultural ethnography domain (spraddley, 1980) was used in the initial analysis of the data took place during the year of observation. concepts of hermeneutic philosophy of Gadamer (1999) as hermeneutics conversion that leads to the understanding that defines the fusion of horizons were used in the analysis of subsequent data collection will. reading reception theory concepts Iser (1978) as errant view of the reader, the primeito and background reading, the meaning and the reading of significance were also used in the analysis. the research is characterized as interdisciplinary, seeking integration between applied linguistics, for studying the language in use; ethnographic anthropology, because its concepts